Performance Evaluation of Parameterizations for Wind Input and Wave Dissipation in the Spectral Wave Model for the Northwest Atlantic Ocean. Issue 4 (7th August 2020) - Lin, Shangfei; Sheng, Jinyu; Xing, Jiuxing
ABSTRACT: An ocean wave model for the northwest Atlantic Ocean based on WAVEWATCH III is used to evaluate four different source term packages (known as ST2, ST3, ST4, and ST6) for the wind input and wave dissipation. The performance of ST2, ST3, ST4, and ST6 is assessed using available measurements from buoy stations and satellite altimeters. The model results for significant wave height ( H s ), mean wave period ( T m 02 ), wave spectrum, wind input, and wave dissipation are examined during two periods: (i) winter storms in February and (ii) Hurricane Ophelia in September/October 2011. Analyses of model results demonstrate that ST4 and ST6 have the best performance with an average scatter index within 19.0% for H s and T m 02 in the presence of strong currents and sea ice. These four packages perform differently under different sea states. Package ST6 generally overestimates H s under the wind-wave-dominated sea states because of strong wind input and fast wave growth but underestimates H s under swell-dominated sea states because of strong swell dissipation. The effects of ocean surface currents and sea ice on the wave model performance are also investigated. The linear kinematic effects of surface currents on waves can cause non-linear dynamic effects, which can differ among the four packages. Wave scattering in sea ice increases the wave directional spread and may cause an increase in H s . In the presence of sea ice, wind input is reduced and shifted to higher frequencies and wave dissipation is further suppressed.